Influence of harvesting methods of aonla (Emblica officinalis Gaertn.) on its physical injury, harvesting efficiency and operational cost - Pathak, P.K.; Dwivedi, Preeti; Kumar, Sunil (Indian Journal of Agroforestry, 2020)
Aonla is an important fruit crop of agroforestry system due to its hardiness, medicinal value and high economic return. Marketability of its fruit depends upon size, appearance and injury to the fruit. Injury of fruits may occur during its harvesting, transport and handling which reduces its cost and postharvest shelf life. Three Aonla cultivars viz. Desi, Chakaiya and NA-7 were harvested using different manual techniques and compared for harvesting efficiency, extent of physical injury and cost. Harvesting efficiency of Aonla cultivars varied from 11.8 to 67. 3kg/ha per worker whereas physical injury ranged from 5.3 to 95.5 per cent and cost of operation was Rs. 0.13 to 0.74 per kg of fruit. All the harvesting parameters were highly significant for selected cultivars and method of operation. Significantly lowest injury was found by hand picking method whereas the lowest cost and the highest harvesting efficiency of workers were found by shaking stem and collecting fruits on cloth sheet held by two workers. In view of these shaking stem and collecting fruits on cloth sheet was recommended as the best possible method for harvesting Aonla fruits under agroforestry system.